2011
DOI: 10.1073/pnas.1100432108
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the sequence–function relation in gene silencing by bacterial small RNAs

Abstract: Sequence-function relations for small RNA (sRNA)-mediated gene silencing were quantified for the sRNA RyhB and some of its mRNA targets in Escherichia coli. Numerous mutants of RyhB and its targets were generated and their in vivo functions characterized at various levels of target and RyhB expression. Although a core complementary region is required for repression by RyhB, variations in the complementary sequences of the core region gave rise to a continuum of repression strengths, correlated exponentially wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 50 publications
(123 reference statements)
6
56
0
Order By: Relevance
“…We found that a 14-nt RNA oligo corresponding to the minimum base-pairing region of SgrS is able to inhibit ptsG translation without the help of Hfq in vitro (Maki et al 2010). More recently, it has been shown that a truncated RyhB in which internal portions other than the base-pairing region are largely deleted is able to repress efficiently the target sodB mRNA in the absence of Hfq in vivo (Hao et al 2011).…”
Section: (B) Properties Of Sgrs-s Variants It1568 Cells Harboring Inmentioning
confidence: 99%
“…We found that a 14-nt RNA oligo corresponding to the minimum base-pairing region of SgrS is able to inhibit ptsG translation without the help of Hfq in vitro (Maki et al 2010). More recently, it has been shown that a truncated RyhB in which internal portions other than the base-pairing region are largely deleted is able to repress efficiently the target sodB mRNA in the absence of Hfq in vivo (Hao et al 2011).…”
Section: (B) Properties Of Sgrs-s Variants It1568 Cells Harboring Inmentioning
confidence: 99%
“…The striking overlap with the previous ptsG data (38) lead us to conclude that the SgrS seed region, a critical RNA element that had already evolved in Salmonella, was acquired for the regulation of the horizontally acquired SopD virulence factor. Successful seed pairing of small RNAs with targets has been proposed to largely depend on the thermodynamic stability of the RNA duplex that is formed (41,42). Accordingly, most target search algorithms, including the popular RNAhybrid , which was established with 10 targets of RybB sRNA (44).…”
Section: A Single G-u Pair Prevents Regulation Of the Nearly Identicamentioning
confidence: 99%
“…The apparent Boltzmann constant, b, has been measured as 0.45 AE 0.05 mol/kcal, which was confirmed in a second study (Hao et al, 2011). In practice, we use a proportional constant of 2,500 to generate a proportional scale where physiological common translation initiation rates vary between 1 and 100,000 au.…”
Section: Models and Computationmentioning
confidence: 79%